Dungeons & Dragons. The book of dragons - Witwer, Michael (DK/Penguin Random House, 2025)
"Delve into the awe-inspiring world of dragons, lavishly illustrated with newly commissioned artworks and penned from the perspectives of Tiamat and Bahamut, the mighty dragon gods themselves. Decades of complex lore are ... condensed into detailed summaries. ... This definitive guide unveils the rich lore, diverse types, and legendary characters of the dragon realm. Essential for every D&D fan, it offers ... insights into these iconic creatures that for decades have been the heart and soul of the game. Elevate your campaigns and deepen your knowledge"--